1996
DOI: 10.1002/etc.5620151027
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented macrophage aggregates: A toxic response in fish exposed to bleached‐kraft mill effluent?

Abstract: Abstract-An epidemiological study was conducted to evaluate whether the density of pigmented macrophage aggregates (PMAs) and the prevalences of preneoplastic and neoplastic lesions increased in fish captured downstream from a bleached-kraft pulp mill, causing induction of cytochrome P4501A enzymes (CYP1A). White suckers (Catostomus commersoni) sampled 10 and 95 km downstream from a bleached-kraft pulp mill in the St. Maurice River, Quebec, Canada, exhibited higher densities of PMAs relative to age in liver, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 28 publications
(52 reference statements)
3
44
0
2
Order By: Relevance
“…A similar effect was previously noted in fish exposed to BKPME (Santos et al, 1990;Couillard and Hodson, 1996). According to Couillard and Hodson (1996), the presence in these effluents of resin acids or other hemolytic compounds may accelerate the rate of erythrocyte destruction, leading to the observed splenic hemosiderosis. The increment in hemolysis may result in a decrease in the number of mature erythrocytes in the circulating blood (Hibiya, 1982).…”
Section: Histological Examinationsupporting
confidence: 76%
See 1 more Smart Citation
“…A similar effect was previously noted in fish exposed to BKPME (Santos et al, 1990;Couillard and Hodson, 1996). According to Couillard and Hodson (1996), the presence in these effluents of resin acids or other hemolytic compounds may accelerate the rate of erythrocyte destruction, leading to the observed splenic hemosiderosis. The increment in hemolysis may result in a decrease in the number of mature erythrocytes in the circulating blood (Hibiya, 1982).…”
Section: Histological Examinationsupporting
confidence: 76%
“…According to Myers et al (1987), this alteration is often associated with a degenerative-necrotic condition. More recently, Couillard and Hodson (1996) studied the proliferation of PMAs in BKPME-exposed fish and suggested that several known toxic effects of these effluents could contribute to this response, including CYP1A induction, toxic hemolysis, and impaired macrophage function. These statements are also applicable to splenic hemosiderosis.…”
Section: Histological Examinationmentioning
confidence: 99%
“…aggregations of MAs, EGCs and epithelioid cells) at the interface between host and parasite. The MAs were observed in histological sections of 14 powan hearts, and their proliferation has been frequently associated with both physiological and pathological factors including starvation, aging, intoxication and the presence of infectious disease (Vogelbein et al 1987, Couillard & Hodson 1996, Couillard et al 1999. The presence of MAs have been reported for Rivulus marmoratus (Poey) experimentally infected with the protozoan Calyptospora funduli Overstreet, Hawkins & Fournie, 1984(Vogelbein et al 1987) and also for Gasterosteus aculeatus infected with the microsporean Glugea anomala (Dezfuli et al 2004).…”
Section: Resultsmentioning
confidence: 96%
“…Hepatic melanomacrophages appear to increase in number also with antigenic stimulation, and with otherfactors causing tissue breakdown [41]. Increased density of these macrophages has also been observed in experimentally treated fish [44], amphibians [45], and naturally polluted frogs [46].…”
Section: Discussionmentioning
confidence: 92%
“…Melanin is a complex polymer that can absorb and neutralize free radicals and other toxic agents [40] [43]. Melanomacrophages are focal accumulations of pigmented macrophages in liver, spleen and more rarely in kidneys of fishes [44] and also in liver of frogs [45]. These may contain four types of brown to black pigments, namely melanin, lipofuscin, ceroid, and hemosiderin/ferritin.…”
Section: Discussionmentioning
confidence: 99%